Effect of a helical core topology on impurity behavior in RFX-mod plasmas. (24th March 2017) - Gobbin, M; Carraro, L; Puiatti, M E; Valisa, M; Franz, P; Momo, B; Terranova, D
Abstract: The effects of non-axisymmetry on the ion distribution of light impurity in the high current plasmas of the reversed field pinch device RFX-mod are investigated. To this end a 1D collisional radiative code has been updated in order to deal with helical shaped plasmas. Numerical simulations reported in this paper focus in particular on the determination of the density of carbon ionization stages with the aim of enlighting the differences between a cylindrical and a helical modeling approach.